Prevalence of Escherichia Coli O157 strain isolated from dairy cattle manure in Bogor, Indonesia - Elsharkawy, Sara; Latif, Hadri; Purnawarman, Trioso; Rahayu, Puji (Revista de Ciências Agroveterinárias, 2025)
In Bogor, Indonesia, where dairy farming is prevalent, dairy cattle manure serves as a significant reservoir for numerous bacteria, including the potentially harmful Escherichia coli. This study intends to evaluate the prevalence of E. coli O157, a particularly pathogenic strain, in 25 manure samples collected from different dairy farms in the Kebon Pedes area of Bogor. This study was conducted from June 2023 to December 2023. Using the Global Tricycle Surveillance ESBL E. coli WHO 2021 method for isolation and identification and employing the SYBR Green real-time polymerase chain reaction (qPCR) technique for E. coli O157 detection, the results revealed that out of 25 E. coli positive samples, three tested positive for E. coli O157, indicating a prevalence rate of 12% of this specific strain. The occurrence of this pathogenic variant suggests a noteworthy finding in understanding the microbial landscape of dairy cattle manure in Bogor. The presence of E. coli O157 in dairy cattle farms underscores the potential for continuous bacterial transmission to the environment, highlighting the importance of ongoing monitoring and comprehension of pathogenic strains in agricultural settings for the development of effective public health strategies. Improved manure management protocols and regular surveillance programs can be used as targeted interventions to mitigate the risks of E. coli O157 transmission from dairy farms.